CONTEMPORARY POLITICAL EPISTEMOLOGY AS A FACTOR IN THE IDENTIFICATION OF CONFLICTUAL METANARRATIVES - Tretiak, Oleksii (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2026)
The article is devoted to clarifying the significance of the political-epistemological dimension of destructive communication metanarratives in the context of studying and analyzing the semantic dimension of digital content. The aim of the study is to establish the potential of political epistemology as a factor in interpreting and identifying disinformation metanarratives. Research methods. The study combines political epistemology with rational-critical discourse analysis and uses structural-functional and institutional perspectives to assess the coherence, validity, and epistemic grounding of metanarratives in political communication and governance. Research results. Ideologized propaganda disinformation aims to undermine trust in official discourse and strengthen political and ideological positions through appeals to the epistemic foundations of collective knowledge. Political-epistemic assessment of metanarratives embedded in propaganda and disinformation reveals their consequences for governance, social stability, and the security of society’s information systems, while also highlighting its functional dimension, namely the organization of information and the establishment of epistemic priorities within the semantic core of the metanarrative. Conflictual metanarratives distort the socio-political world through framing, emotional appeals, selective evidence, and repetition as instrumental means of asserting false theses or concepts. Rational-critical discourse analysis offers tools for studying the structural capacity of political language and discourse, while political-epistemic assessment makes it possible to identify biases, hidden assumptions, and ideological motives embedded in institutions of political representation and governance. One of its promising missions, especially in modern Ukraine, is the formation of an environment of “epistemic vigilance.” Discussion. It is argued that the ability of society to politically and epistemically evaluate the applied conflict metanarratives is of strategic importance for political governance, social cohesion, and information security Conclusions. It is established that the metanarrative is an appeal to a certain “political truth”, which has a biased (ideologized) nature and aims to structure digital media messages of a lower order. It is concluded that in the conditions of Russian aggression, the political-epistemic examination of conflict metanarratives is designed to create an “intellectual network” for the formation of information sovereignty and information immunity of Ukrainian society and the state.